2020
DOI: 10.4018/978-1-7998-3576-9.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Corralling Contract and the Land Use Relationship Between Pastoralists and Agriculturalists in Nigeria

Abstract: “Corralling contract” is the indigenous fertilization system commonly practiced in the African Sahel and its southern periphery. In this chapter, the practice of the corralling contract between Fulani pastoralists and Nupe agriculturalists in the Bida region of Niger State of central Nigeria is examined. The study attempts to find out how the farmers and herders arrange the corralling contract, how they utilize this instrument, and how it influences their social relationship. Findings suggest that pastoral Ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have also reported establishment of manure and crop residue contracts between Sahelian transhumant pastoralists and crop farmers in southern Niger and Nigeria (Hoi Yee Fu, 2020). This practice consists of allowing pastoralist herds to graze on crop farmers’ fields after grain harvest, and in return, crop farmers benefit from animal dung and urine as manure for their soils.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have also reported establishment of manure and crop residue contracts between Sahelian transhumant pastoralists and crop farmers in southern Niger and Nigeria (Hoi Yee Fu, 2020). This practice consists of allowing pastoralist herds to graze on crop farmers’ fields after grain harvest, and in return, crop farmers benefit from animal dung and urine as manure for their soils.…”
Section: Introductionmentioning
confidence: 96%